An analysis of Miguel's family identity in Lee Unkrich's Coco (2017) - Jeriko Passa Bakti Nugroho; Tri Pramesti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the family identity of Miguel Rivera as portrayed in the script of Coco (2017), written by Lee Unkrich and Adrian Molina. Two central questions guide the research: what conflicts Miguel faces in connection with his family identity, and how he comes to understand and discover his true family identity throughout the narrative. The theoretical foundation of this study is drawn from Erik Erikson's framework of psychosocial development, with particular focus on the stage known as Identity vs. Role Confusion, which addresses the struggle between externally imposed roles and an individual's own developing sense of self.The study adopts a qualitative approach, employing content analysis as its method of inquiry. The data consist of selected dialogues, character actions, and narrative sequences taken directly from the script of Coco (2017), chosen for their relevance to Miguel's experience of family identity conflict and discovery. The scope of analysis is intentionally focused on Miguel Rivera as the central character, with other characters treated as supporting figures rather than independent subjects of study.Two primary findings emerge from the analysis. To begin with, Miguel's conflicts with his family identity follow an escalating pattern rooted in the Rivera family's long-standing prohibition of music, a prohibition that operates as a form of identity foreclosure, denying Miguel the space to explore who he genuinely is. These conflicts grow in intensity as the story progresses, moving from quiet suppression at home to conditional blessings that require Miguel to surrender his sense of self entirely. Additionally, Miguel's path toward understanding his family identity proves to be neither sudden nor solitary. It unfolds gradually through his relationships with Ernesto de la Cruz, Héctor, and his ancestors, each encounter dismantling a layer of the false identity he had constructed until he arrives at the truth: that his family identity was never built on the rejection of music, but on the quiet devotion of a man named Héctor who only ever wanted to go home.The study concludes that the script of Coco offers a nuanced and emotionally resonant portrayal of family identity formation, one that speaks directly to the concerns at the heart of Erikson's theoretical framework. Miguel's journey makes clear that a genuine sense of family identity is not something that can be inherited without question or escaped without consequence. It must be sought, tested, and ultimately chosen.